2011
DOI: 10.6090/jarq.45.181
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Feral Populations of Brassica napus Originated from Spilled Seeds around the Kashima Seaport in Japan

Abstract: Concern has been raised about the importation and transportation of GM B. napus, because feral herbicide-tolerant GM B. napus plants have been found growing around some major seaports in Japan. We should monitor the persistence of these feral B. napus populations including the herbicide-tolerant GM cultivars to prevent the negative impact of GM B. napus on native plant communities. In this study, we examined the plant numbers and the persistence of the B. napus at 19 sites around the Kashima seaport in Japan o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and those from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occur at the same location over successive years, but the majority of plants did not survive, resulting in rapidly declining populations Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2010;Nishizawa et al, 2009;Mizuguti et al, 2011;Squire et al, 2011;Banks, 2014;Katsuta et al, 2015). Moreover, feral oilseed rape populations do not spread by gradual movement out from the sites of initial colonisation (Banks, 2014).…”
Section: Points Raisedmentioning
confidence: 64%
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and those from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occur at the same location over successive years, but the majority of plants did not survive, resulting in rapidly declining populations Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2010;Nishizawa et al, 2009;Mizuguti et al, 2011;Squire et al, 2011;Banks, 2014;Katsuta et al, 2015). Moreover, feral oilseed rape populations do not spread by gradual movement out from the sites of initial colonisation (Banks, 2014).…”
Section: Points Raisedmentioning
confidence: 64%
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and data from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occurs at the same location over successive years, but the majority of plants did not survive, resulting in rapidly declining populations Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2009;Nishizawa et al, 2009;Mizuguti et al, 2011;Squire et al, 2011). However, if habitats are disturbed on a regular basis by anthropogenic activities such as mowing, herbicide applications or soil disturbance, or natural occurrences such as flooding, then feral populations can persist for longer periods (Claessen et al, 2005a;.…”
Section: Population Demography and Factors Contributing To Persistencementioning
confidence: 76%
“…The feral plants probably originated from spillage of contaminated OSR seed from freight trains (Hecht et al, 2014;Schulze et al, 2014Schulze et al, , 2015. Spillage of GM OSR seeds along transportation routes was also confirmed in Japan where cultivation of GM OSR is also prohibited (Saji et al, 2005;Kawata et al, 2009;Nishizawa et al, 2009Nishizawa et al, , 2010Aono et al, 2011;Mizuguti et al, 2011), the United States (in North Dakota 80% of feral OSR proved to be GM: Schafer et al, 2011;Sagers et al, 2012) and Canada (Yoshimura et al, 2006;Knispel et al, 2008;Beckie and Warwick, 2010;Knispel and McLachlan, 2010). Consequently, transportation and handling activities during import of GM OSR are considered the main cause of unintended occurrence and establishment of feral GM OSR in countries without GM OSR cultivation.…”
Section: Oilseed Rape As a Model System For Seed Spillage Along Transmentioning
confidence: 83%